Correcting double outward box distributed residuals by WCEV. Issue 19 (2nd October 2017) - Çelik, Reşit
ABSTRACT: Double outward box distributed residuals are another type of non monotonic heteroscedasticity that severely violates homoscedasticity assumption. In this study Çelik's (2015 ) WCEV is applied to double outward box distributed residuals to provide homoscedasticity for simple and multiple regression models.